(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the effectiveness of vacuum assisted closure (VAC) dressing as a pretreatment of spilt thickness skin grafting versus routine normal saline dressings. Study Design: Randomized control study Place and Duration of Study: This study was conducted at the Department of Plastic and Reconstructive Surgery, Liaquat National Hospital, Karachi from June-December, 2017. Materials and Methods: All patient fulfilling the inclusion and exclusion criteria were asked for a consent and enrolled in the study. Patient of either sex, age, from 20 – 50 years with traumatic and post-surgical acute wounds (within a week) on upper or lower limbs only, requiring split thickness skin grafting were included in the study. Statistical package for social sciences (SPSS) version 18 was used for data analysis. Chi-square test was used for significant co-relations with 95% confidence interval. Results: A total of 92 patients with traumatic and post-surgical acute wound requiring spilt thickness skin grafting were included in this study. Forty six in group A were treated by vacuum assisted closure (VAS) and 46 were treated with normal saline Effectiveness was significantly higher in group A than group B (80.4% vs. 56.5%; p=0.014). Conclusion: Split-thickness skin grafting provides a simple one-stage reconstructive option for skin and soft tissue defects. The use of VAC therapy is an effective and a safe adjunct to conventional treatment modalities for the management of wound.